Իրանահայ գեղանկարչութիւնը XX դարում (համառօտ ակնարկ) - Բաբայեան, Անի (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
This article provides a brief overview of the history of painting in Iran in the twentieth century, introducing Armenian Iranian painters whose works reflect the interaction and fusion of Armenian traditional artistic styles with contemporary Persian and European styles. Iranian painting in the twentieth century developed in three directions: Realism, Traditional Painting, and Modern. Armenian artists whose works are the best examples of Armenian and Iranian interaction are presented.
Keywords: History of painting; Iran